Physical attractiveness, candidate demeanor, name desirability and voters' preference for their candidates in the National elections - Abadilla, Andrea Lyn; Bautista, Anna Merin (2001)
Past studies provided us with several insights regarding the determinants of candidate preference. Many studies have been devoted to such factors as ethnicity, socioeconomic status is "the single most important influence in citizen participation may hold true for other countries, but may not hold true for ours. We must therefore consider the Philippine setting as well, taking note that the attitudes, beliefs and opinions of voters here may vary with those of people in other settings. In Philippine politics, a casual observer may note that candidates mat be elected to office due to their popularity and physical attributes. Hence, they studied attraction as a determinant of candidate preference. This study would like to verify if attraction does in fact play a part in a Filipino voter's preference for a candidate. The study was conducted in the form of survey with individual voters as the unit of analysis. The respondents were selected via random sampling from the voters list of the May 1998 elections.The result showed that Filipino voters' preference of candidates is significantly affected by their attraction to them. The results showed that the respondents consider, among other things, the Demeanor of a candidate when choosing whom to vote. The results of the study also show that some factors that had been seen as the most important in determining candidate preference may not necessarily be so. Variables such as ethnicity and socioeconomic status had no significant relationship with candidate preference -- Author's abstract.